Tryptophan Synthase: Biocatalyst Extraordinaire - Watkins-Dulaney, Ella (Chembiochem, 2020)
Tryptophan synthase (TrpS) has emerged as a paragon of noncanonical amino acid (ncAA) synthesis and is an ideal biocatalyst for synthetic and biological applications. TrpS catalyzes an irreversible, C–C bond-forming reaction between indole and serine to make l-tryptophan; native TrpS complexes possess fairly broad specificity for indole analogues, but are difficult to engineer to extend substrate scope or to confer other useful properties due to allosteric constraints and their heterodimeric structure. Directed evolution freed the catalytically relevant TrpS β-subunit (TrpB) from allosteric regulation by its TrpA partner and has enabled dramatic expansion of the enzyme’s substrate scope. This review examines the long and storied career of TrpS from the perspective of its application in ncAA synthesis and biocatalytic cascades.